2020
DOI: 10.1186/s13045-020-00964-5
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes with sequential FLT3-inhibitor-based therapies in patients with AML

Abstract: Background Second-generation FLT3-inhibitors (FLT3i) demonstrated single-agent composite CR rates (CRc) of 45–55% in patients with relapsed/refractory (R/R) FLT3-mutated AML in phase II/III trials. However, > 85% of patients treated were prior FLT3i naïve. The response rates to sequential FLT3i exposure remain poorly defined. Methods We retrospectively reviewed patients with FLT3-mutated AML between November 2006 and December 2019. Results In frontline patients treated with a FLT3i (cohort 1), the CRc r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In the frontline setting, there was a sequential decrease in CRc rates (77%→31%→25%) and OS (16.7→6.0→1.4 months). A comparable decrease in CRc rates (45%→21%→10%) and OS (7.9→4.0→4.1 months) was observed with sequential FLT3i-based therapies in the R/R AML setting 73 . Perl and colleagues investigated whether prior FLT3i therapy influenced outcomes in patients treated with gilteritinib.…”
Section: Future Directionsupporting
confidence: 53%
“…In the frontline setting, there was a sequential decrease in CRc rates (77%→31%→25%) and OS (16.7→6.0→1.4 months). A comparable decrease in CRc rates (45%→21%→10%) and OS (7.9→4.0→4.1 months) was observed with sequential FLT3i-based therapies in the R/R AML setting 73 . Perl and colleagues investigated whether prior FLT3i therapy influenced outcomes in patients treated with gilteritinib.…”
Section: Future Directionsupporting
confidence: 53%
“…It should also be noted that there was greater availability in our cohort of salvage therapies incorporating new and investigational FLT3i based combinations, which may have also contributed to improved outcomes among those patients who did not receive FLT3i in the frontline and may be improving survival in those not undergoing SCT. 29 The incorporation of FLT3i into the frontline regimens may be playing an important role in improving outcomes with respect to the historically adverse prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the duration of FLT3 TKI efficacy after several courses of the drugs, a recent retrospective study reported the outcome of FLT3-mutated AML patients who received sequential courses of FLT3 TKI because of AML relapse [ 62 ]. In this trial, 239 patients receiving FLT3 TKI for the first time, either as front-line treatment (56 patients) or as a salvage treatment for an R/R AML (183), were enrolled.…”
Section: Perspectivesmentioning
confidence: 99%